A NEW METHOD IN THE IDENTIFICATION OF NOISE AND VIBRATION CHARACTERISTICS OF AUTOMOTIVE DISK BRAKES IN THE LOW FREQUENCY DOMAIN - Hassan, Muhammad Zahir; Magaswaran, K.; Phuman Singh, A.S. (Universiti Malaysia Pahang, 2014)
Noise and vibration characterization is an important benchmark to reduce brake noise.Brake noise and vibration measurement is commonly done on an actual vehicle or on a brake dynamometer. A full scale brake dynamometer takes into account the attached mass which resembles the mass of a quarter scale vehicle. This paper proposes a testing method which eliminates the need for attached masses. This is achieved through the scaling of the brake system parameters to accommodate the loss of mass and produce similar conditions to those in actual braking. The measurement of noise and vibration is measured simultaneously and an FFT is performed to identify the frequencies of noise and vibration. An experimental modal analysis (EMA)is done to obtain the frequencies which the brake system tends to produce as a validation to the proposed method. It is shown that through this method the noise and vibration characteristics of the brake system and the unstable frequencies can be identified.